2017
DOI: 10.3847/1538-4357/aa5f16
|View full text |Cite
|
Sign up to set email alerts
|

Microphysics in the Gamma-Ray Burst Central Engine

Abstract: We calculate the structure and evolution of a gamma ray burst central engine where an accreting torus has formed around the newly born black hole. We study the general relativistic, MHD models and we self-consistently incorporate the nuclear equation of state. The latter accounts for the degeneracy of relativistic electrons, protons, and neutrons, and is used in the dynamical simulation, instead of a standard polytropic γ-law. The EOS provides the conditions for the nuclear pressure in the function of density … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…The simulations were performed on the Cray supercomupter cluster, typically using 16 nodes, and the message-passing interface supplemented with the hyperthreading technique was used, similarly as in Janiuk (2017). The code is supposed to conserve the axi-symmetry of the initial state, which we confirm.…”
Section: D Computationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The simulations were performed on the Cray supercomupter cluster, typically using 16 nodes, and the message-passing interface supplemented with the hyperthreading technique was used, similarly as in Janiuk (2017). The code is supposed to conserve the axi-symmetry of the initial state, which we confirm.…”
Section: D Computationsmentioning
confidence: 98%
“…We performed 1D to 3D hydrodynamical simulations of the non-magnetized accreting gas on the fixed background using the HARMPI 1 computational code (Ressler et al 2015(Ressler et al , 2017McKinney et al 2012;Tchekhovskoy et al 2007;Mignone & McKinney 2007;Janiuk et al 2013;Janiuk 2017) based on the original HARM code (Gammie et al 2003;McKinney & Gammie 2004). The background spacetime is given by the stationary Kerr solution.…”
Section: Numerical Setupmentioning
confidence: 99%
“…The large-amplitude variability κ and λ classes are not observed as often (Belloni et al 1997a,b). The origin of such large amplitude variability is usually associated with the radiationpressure instability due to its persistently high, near-Eddington mass accretion rate (Janiuk et al 2000). In another approach, Nayakshin et al (2001) showed that a modified viscosity law could reproduce large-amplitude variability qualitatively.…”
Section: Introductionmentioning
confidence: 99%
“…The hole itself should also fastly rotate, in order to efficiently transport the power to the remote jets. Both Blandford-Znajek process and neutrino anihillation may act as the source of this power, and in these two mechanisms their efficiency is similarly scaled with the agnes@cft.edu.pl arXiv:1810.05261v1 [astro-ph.HE] 11 Oct 2018 black hole spin Liu et al 2015;Janiuk 2017). The process is further mitigated by the magnetic fields.…”
Section: Introductionmentioning
confidence: 99%